Tunable ultrasensitive terahertz sensor based on complementary graphene metamaterials. Issue 57 (31st May 2016) - He, Xunjun; Zhang, Qinfei; Lu, Guangjun; Ying, Guobing; Wu, Fengmin; Jiang, Jiuxing
Abstract : In this paper, we propose an ultrasensitive terahertz sensor based on the complementary graphene metamaterial composed of wire-slot and split-ring resonator slot array structure. Abstract : In this paper, we propose an ultrasensitive terahertz sensor based on the complementary graphene metamaterial composed of wire-slot and split-ring resonator slot array structure. The destructive interference between two resonators gives rise to a reflection peak enabling ultrasensitive sensing, and a sensitivity of 177.7 GHz per RIU and FOM of 59.3 can be obtained for the proposed sensor. More importantly, this sensor can not only enhance the absorption of biomolecules and sensing performance, but also dynamically tune the sensing range by shifting the Fermi energy. In addition, the influences of the lateral displacement on the sensing performance are also investigated to improve the sensitivity of the sensor. Therefore, this method opens up opportunities for efficiently sensing several organic and explosive molecules and biomolecules.